Impact of Al2O3 and Dy2O3 substitution on the physical, structural and radiation shielding properties of Li2O-B2O3 glass system - Aljewaw, O.B.; M.K.A Karim,; M.H.M Zaid,; M.K. Halimah,; N.M Noor,; Mhareb, M.H.A.; Alajerami, Y.S. (Penerbit Universiti Kebangsaan Malaysia, 2021)
A new series of lithium-borate glass systems (23Li2O-72B2O3 in mol%) were synthesized with the substitution of Al2O3 (5 mol.%) as a modifier and doped with 0.3 and 0.5 mol% of Dy2O3. Four series of glasses (S1, S2, S3 and S4) were synthesized via the conventional melt-quenching technique and characterized by using UV-Visible-NIR absorption spectrometer and Fourier transform infrared (FTIR) spectroscopy. The current investigation gives further insight on the structural and optical properties of the samples. The diffraction spectrum obtained from the X-ray Diffraction (XRD) analysis shows no typical peaks in the glass system, which indicates its amorphous phase. The optical properties of Al3+ and Dy3+ ions were evaluated and found that there is a pivot effect for the addition of Al2O3 and Dy2O3 for the glass system. Notably, the sample S2 shows different behaviours for physical, structural, and optical properties compared with other prepared glass samples that can be attributed to the increment of Al2O3. Besides, the physical and ionizing shielding features were investigated for current glass samples. The radiation shielding properties were examined within the energy range of 0.015 until 15 MeV. The sample S4 has the optimum radiation shielding features as a result of the addition of Dy2O3. Hence, the composition attributes a new glass system that can be used in various applications such as radiation dosimeter and photon shielding materials.